Pålsjö forest : actual situation and evaluation of the forest management - Moscoso, John (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
According to the Statistic Central Bureau the municipality of Helsingborg has 122.000 inhabitants and the green areas close and around 5 Km downtown are very scarce. In the Reconnaissance maps of 1820, a big area in the northern part of the town of Helsingborg was covered with agricultural lands. Today all these areas has been built and Pålsjö is located right away in the northern part of the town. Pålsjö forest is one of the most used and impacted green areas in Helsingborg. Almost everyone knows and uses the area very often, and this severe use added to the air pollution caused by traffic and industry is impacting this green area.